PENERAPAN GAME DADU DAN FLASHCARD UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA PADA MURID KELAS III SD - Hanif Achmad Fianto Aji; Ina Agustin; Ani Juniatik (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to improve the learning outcomes of Pancasila Education through the application of Dice and Flashcard Games in third grade students of Mondokan State Elementary School. This study uses the Class Action Research (PTK) method of the Kemmis and McTaggart models which is carried out in three cycles. The research subjects amounted to 29 grade III students. Data collection techniques are carried out through observation, testing, and documentation. Data are analyzed descriptively, quantitatively, and qualitatively. The results of the study showed an increase in student learning outcomes in each cycle. In the pre-cycle stage, the average student learning outcome was 68 with 51.7% learning completeness. In the first cycle, the average learning outcome increased to 74 with learning completeness of 62.1%. Furthermore, in cycle II, the average learning outcome increased to 80 with learning completeness of 75.9%. In cycle III, the average learning outcome increased to 89 with learning completeness reaching 89.7%. In addition to improving learning outcomes, the use of Dice and Flashcard Games also increases student activity, motivation, and engagement during the learning process. Thus, Dice and Flashcard Games are used effectively to improve the learning outcomes of Pancasila Education for third grade elementary school students.